A Study of the Ballistic Limit of AA2024-T351 Sheets Impacted by Spherical and Cubical Compact Projectiles - DE VUYST, Tom; VIGNJEVIC, Rade; AZORIN ALBERO, Adrian; HUGHES, Kevin; CAMPBELL, James C.; DJORDJEVIC, Nenad (Engineering Transactions, 2016)
This paper presents the results of an investigation of the ballistic limits and failure modes of AA2024-T351 sheets impacted by spherical and cubical projectiles. The investigation included a series of impact experiments and numerical simulations. The lowest ballistic limit (225 m/s) was observed for the spherical projectile. In the cube impacts the ballistic limit was 254 m/s. With the aid of the finite element models it was possible to develop a better understanding of the test results and explain that the observed differences in the impact responses are due to the combination of the localised deformation near the projectile impact point and the resulting global, dishing, deformation.